O08.3 Rates of chlamydia and gonorrhea testing and positivity before and after initiation of PrEP among MSM in US private settings. (14th July 2019) - Tao, Guoyu; Pearson, William; Sullivan, Jane; Henk, Henry; Gift, Thomas
Abstract : Background: The Centers for Disease Control and Prevention (CDC) recommends initial and follow-up STD and HIV testing when taking HIV pre-exposure prophylaxis (PrEP). We assessed frequencies of STD and HIV testing and rates of STDs among men who have sex with men (MSM) taking PrEP. Methods: We used the OptumLabs® Data Warehouse (OLDW) a comprehensive, longitudinal, real-world data asset with de-identified people from a national U.S. insurance plan. Male patients aged ≥ 18 years were identified as MSM if patients had rectal chlamydia or gonorrhea tests or had an ICD-10 code for high-risk homosexual or bisexual behavior in 2016–2017. Initiation of PrEP was defined as the first date of tenofovir plus emtricitabine (Truvada) prescription in 2016–2017 if they had no previous HIV or HBV infection and had no PrEP prescription before 2016. Continuous use of PrEP was defined if there were no 14 day gaps between prescriptions. We measured STD and HIV testing in MSM who continuously used PrEP for ≥ 180 days. Results: Of 682 MSM who initiated PrEP in 2016–2017 and continuously used PrEP for ≥180 days, chlamydia, gonorrhea, and HIV testing was 61.4%, 61.4%, and 51.3%, respectively, at 6 month follow-up. These percentages were significantly lower than testing in the same patients at PrEP initiation (67.6%, 67.6%, and 57.2%, respectively, p < 0.01). Chlamydia and gonorrhea positivity in MSM who were tested at 6 month follow-up was 10.0% and 9.5%, respectively, versus 6.1% and 6.7%, respectively, at PrEP initation. Conclusion: MSM on PrEP are at high risk for chlamydia and gonorrhea. STD testing at 6 month follow-up for MSM who are continuously enrolled on PrEP is sub-optimal, but that STD positivity increases versus the baseline, suggesting elevated risk. Interventions to improve provider adherence to screening recommendations in the CDC STD treatment guidelines for MSM on PrEP are urgently needed. Disclosure: No significant relationships.